La “ayuda familiar” como medida de fomento del empleo y/o del autoempleo en tiempos de crisis: estado de la cuestión en España y propuestas de reforma - Barrios Baudor, Guillermo L. (Revista de Derecho, 2019)
In not few cases, autonomous workers receive formal and/or informal help from their closest relatives. Therefore, on the basis of Spanish legal ordainment, the present work has as its main objective to present the granting of services in the modality of “family help or collaboration” as a real employment and/or self-employment opportunity in times of crisis. More specifically, what we pretend to do is but highlight the virtuality of family collaboration in generating formal employment (in contrast to the frequently informal), whether in the modality of paid employment or in self-employment. In no way should it be regarded as a second class modality of service granting.